Organisational readiness of nursing education institutions to integrate students who have disabilities into nurse education institutions (NEIs) training programmes: A case study of Kwazulu-Natal NEIs. (2020) - Moodley, Selvarani; Mchunu, Gugu
Abstract: Background: The efforts of nurse educators to include student nurses who have disabilities (SNWDs) in nurse training may have a limited significance when the organizational readiness of nursing education institutions (NEIs) is not adequately prepared to meet the needs of SNWDs. Objectives: To explore and describe the organisational readiness of selected NEIs in KwaZulu-Natal, South Africa to include SNWDs in nurse training programs. Methodology: A qualitative design using a case study approach was adopted to meet the objectives of this article. A three-step sampling method was used to select three private NEIs and one university as the cases. Content analysis was used to analyse the data. Results: Two themes emerged as to the support provided and barriers to inclusion for SNWDs in nurse training. The findings of the study reveal that support was provided at the discretion of individual NEIs and individual educators largely due to the absence of policy guidelines specific to including students with disabilties (SWD) in nurse training programmes. Barriers to inclusion include infrastructure challenges, lack of resources, and limited knowledge of nurse educators. Conclusion: NEIs have limited readiness to include SNWDs in nurse training resulting from a lack of access to lectures by SNWDs due to structural barriers, lack of funding and lack of resources to accommodate SNWDs. NEIs require adequate funding to provide an organizational environment inclusive of SNWDs. NEIs should consult the National Student Financial Aid Scheme for funding (NSFAS) and capacitate educators on disability matters concerning SNWDs.